Loss of human leukocyte antigen expression on colorectal tumor cell lines: implications for anti-tumor immunity and immunotherapy. - Browning, M; Krausa, P; Rowan, A; Hill, AB; Bicknell, D; Bodmer, J; Bodmer, W (1993)
A system devised for tissue typing the human leukocyte antigen-A (HLA-A) locus from genomic DNA by the polymerase chain reaction (PCR) has been used to investigate abnormalities of HLA expression in a panel of 30 cell lines derived from colorectal adenocarcinomas, by comparison of the HLA-A locus genotype with surface expression of HLA. Eleven cell lines gave single HLA-A locus specificity on PCR typing, suggesting that loss of HLA alleles is a common abnormality. In one of these cell lines the loss of an HLA-A locus allele was confirmed by comparison with DNA from a lymphoblastoid B cell line derived from the same patient. In three cell lines, loss of expression of an HLA-A locus determinant was observed in spite of the presence of the relevant allele in genomic DNA. Three cell lines showed absent HLA expression associated with failure to express beta 2-microglobulin. These data indicate that at least three independent mechanisms were involved in the loss of HLA expression on the colorectal tumor cell lines.